-1
$\begingroup$

I have no idea how to prove following identity: $$ \sum_{n=2}^{\infty}\frac{2}{(n^3-n)3^n}=-\frac{1}{2}+\frac{4}{3}\sum_{n=1}^{\infty}\frac{1}{n\cdot3^n} $$

My main problem concerned the fact, that I had not clear idea in what direction should my efforts go in order to find solution. I did try to use partial sums in similar vein as Stuart Gordon, but it was far from being successful.

$\endgroup$
  • 1
    $\begingroup$ The identity is not true, there should be a misprint. $\endgroup$ – Start wearing purple Jan 1 '16 at 13:53
  • 2
    $\begingroup$ See my answer below, it should be $n$, not $n^3$. $\endgroup$ – Ron Gordon Jan 1 '16 at 13:56
  • $\begingroup$ In this community, I am ready to bet that, once more and not surprizingly, Ron Gordon is right. As Start wearing purple also commented, there is one more typo in a textbook. Happy New Year !! $\endgroup$ – Claude Leibovici Jan 1 '16 at 15:03
4
$\begingroup$

Use partial fractions...

$$\begin{align}\sum_{n=2}^{\infty} \frac{2}{(n^3-n) 3^n} &= \sum_{n=2}^{\infty} \frac{1}{(n-1) 3^n} + \sum_{n=2}^{\infty} \frac{1}{(n+1) 3^n} - \sum_{n=2}^{\infty} \frac{2}{n 3^n} \\ &=\frac13 \sum_{n=1}^{\infty} \frac{1}{n 3^n} + 3 \sum_{n=3}^{\infty} \frac{1}{n 3^n} - \sum_{n=2}^{\infty} \frac{2}{n 3^n} \\ &= \frac43 \sum_{n=1}^{\infty} \frac{1}{n 3^n} - 3 \left (\frac13 + \frac1{18} \right ) + \frac23 \\ &= \frac43 \sum_{n=1}^{\infty} \frac{1}{n 3^n} - \frac12 \end{align}$$

This is a log, so that the sum is actually

$$\sum_{n=2}^{\infty} \frac{2}{(n^3-n) 3^n} = \frac43 \log{\frac32} - \frac12 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.